Thailand Pavilion Design for World Expo 2020 Dubai - Jagoonchorn, Wachirapong; Horayangkura, Vimolsiddhi (Journal of Architectural/Planning Research and Studies (JARS), 2022)
For over 150 years, Thailand has participated in world-class events such as the World Expo. Every event has been presented in association with traditional Thai architecture, reflecting Thai identity in the Thailand Pavilion. In the World Expo 2020 Dubai, the United Arab Emirates, the main theme of the event is “Connecting Minds, Creating the Future.” The objective of this study is to create and present the architecture of Thailand Pavilion to be conformed with the main theme regarding the image of being a modernized nation and in accordance with the policy of Thailand 4.0. The Thailand Pavilion in a contemporary style is appropriate to the high temperature environment of Dubai. It Includes the introduction of innovative technology to be used in both construction and display of exhibition. This research aims to reflect the development and presentation of Thailand through architecture. Thailand Pavilion building in World Expo 2020, Dubai, the United Arab Emirates, covers various aspects regarding fundamentals of Thai architectural identity, the historiography of Modern Architecture in Thailand, Thailand pavilions in the past, building design in high temperature country, and circulation pattern in the exhibition building. It would contribute to the mindsets of all participants and Thai architects in particular regarding the creative architectural design of modern Thailand.